Job Stress and Journalists Productivity in the Workplace - Nwokeocha, Ifeanyi Martins (International Journal of Religion Education and Law, 2024)
This paper discusses various aspects of job stress and other stress related issues within the context of work situations in Nigeria. It examines the different types of stress and the myriads of factors that may cause stressful conditions in the Nigerian workplace. It also looks at the physiological, psychological and physical effects of job stress and proffers some preventive measures and coping strategies. The paper concludes that the growing incidences of job stress in Nigeria needs to be addressed, as its impact in the ambience of depressing socio-political and economic conditions can be nothing other than debilitating and destabilizing to the nation and its workforce. However, the study concluded that Employers of journalists should take the issue of stress management very seriously as many journalists experience different degrees of stress. Management of various organizations in which journalists serve should endeavour to organize seminars on stress management to enable them learn stress coping strategies.